Solvothermal synthesis of vanadium phosphate catalysts for n-butane oxidation - Rownaghi, Ali Asghar; Yap, Taufiq Yun Hin; Rezaei, Fateme (Elsevier, 2009)
In this paper, we have developed a simple, low-cost, template-free and surfactant-free solvothermal process for synthesis of vanadyl hydrogen phosphate hemihydrate (VOHPO4·0.5H2O) with well defined crystal size. The synthesis was performed by reaction of VPO4·2H2O with an aliphatic alcohol (isobutyl alcohol, 1-pentanol, 1-hexanol, 1-heptanol or 1-decanol). This afforded well crystallized VOHPO4·0.5H2O by solvothermal methods at 120 °C temperature. This new method significantly reduced the preparation time and lowered production temperature (50%) of catalyst precursor (VOHPO4·0.5H2O) when compared to conventional hydrothermal synthesis methods. By varying the reducing agent, the solvothermal evolution process from layered tetragonal phase VOPO4·2H2O to orthorhombic phase VOHPO4·0.5H2O was observed. It was found that the length of carbon chain in an alcohol in the solvothermal condition had a great impact on chemical and physical properties of resulting catalysts. Interestingly, there was no trace of VO(H2PO4)2 an impurity noted to be readily formed under solvothermal preparation condition. Therefore, this study introduces a more facile synthetic pathway to V(III) compounds. In addition, the microwave-synthesized catalysts exhibited some properties superior to those of conventionally synthesized catalyst such as better stability, crystallinity, and catalytic activity in the production of maleic anhydride. The characterization of both precursors and calcined catalysts was carried out using X-ray diffraction (XRD), inductively coupled plasma-atomic emission spectrometer (ICP-AES), N2 physisorption, temperature programmed reduction (H2-TPR) and scanning electron microscopy (SEM). The XRD pattern of the active catalyst prepared by this solvothermal method confirmed the presence of smaller crystal size (between 6 and 13 nm along 0 2 0 planes) of vanadium phosphate catalyst with higher specific surface area. Finally, the yield of maleic anhydride was significantly increased from 29% for conventional catalyst to 44% for the new solvothermal catalyst.